Status of bacterial colonization in teeth associated with different types of pulpal and periradicular disease: A scanning electron microscopy analysis - Yan-Hua Huang; Si-Jing Xie; Nan-Nan Wang; Jiu-Yu Ge (Elsevier, 2015)
Background/purpose: The purpose of this study was to use scanning electron microscopy (SEM) to investigate the status of bacterial colonization in differently infected root canals and the damage to radicular dentin. Materials and methods: Twenty-five freshly extracted teeth were selected for this study (Group A: 8 teeth with pulpitis; Group B: 10 teeth with periapical lesions; and Group C: 7 teeth with failed root canal treatment). After fixation, the teeth were longitudinally split into two halves. The halves were then dehydrated, sputter-coated with gold, and viewed using SEM, descriptively dividing their lengths into apical, middle, and coronal thirds. Results: In Group A, bacterial infection was mainly located in the coronal third of the root canals and bacteria failed to penetrate into the dentinal tubules. In Group B, bacterial infection was distributed over the entire length of the root canal. The invasion depth of bacteria into the dentinal tubules was approximately 300 μm. In Group C, bacterial infection was mainly focused on the apical third of the root canals. Most of the dentinal tubules had collapsed, and the root canal walls were heavily colonized with dense bacterial biofilm, primarily consisting of cocci. Compared to Group B, the invasion depths were deeper in the apical thirds of root canals (P < 0.05). Conclusion: Bacterial infection was lighter in the root canals with pulpitis than in those with apical periodontitis, which might require special considerations regarding different stages of pulp and periapical pathology in root canal treatment.